AN ISLAMIC ASSESMENT OF INTER-MARRIAGE BETWEEN TANGALE-WAJA AND HAUSA-FULANI COMMUNITIES IN GOMBE STATE, NIGERIA - Ishiaku, Abdulrasheed (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2023)
Marriage as the only legitimate institution that guarantee procreation, play a vital role in promoting strong mutual and cordial relationship between ethnic groups. Gombe State originated from the fusion of two distinct large groups of the Gombe Emirate in the North and the ethnic grouping in the South, known as Tangale-Waja. Therefore, the paper is an Islamic assessment of inter-marriage between Tangale-Waja and Hausa-Fulani communities in Gombe State. It gives a brief account of the Tangale-Waja and Hausa-Fulani communities of Gombe State, their marriage rites and practices, impact and challenges of Inter-marriage between them were also discussed. Qualitative methodology was adopted for the research because of its suitability. Interview was used as instrument for obtaining primary data. The research found out that some families among the Tangale-Waja Tribes and the Hausa-Fulani Communities of Gombe State still frown at inter-ethnic marriages because of the challenges that occur frequently even though could be eradicated with time with the rising number of inter-marriages among them nowadays. To this end, the research concludes that Islam does not in any way make any tribe to be a sign of elevation or prestige and Islam came in order to level all distinctions and does not limit marriage relationship to tribe. Marriage should be based on love, sympathy and affection between the couple.